PREDICTING CASUALTY-ACCIDENT COUNT BY HIGHWAY DESIGN STANDARDS COMPLIANCE - Arief _ Rizaldi; Vinayak _ Dixit (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2016)
Abstract Compliance to standard has been the main doctrine in highway design, but its relationship with accident count has not been widely scrutinized. One of the key programs in road safety in Indonesia is road-worthiness test which assesses the compliance of a road to national design specifications and criteria. In light of current improvements in the crash data system in Indonesia, this study is carried out to develop a model to predict the accident count per type of crashes and to identify significant road features based on their compliance to a national standard. About 272,200 kilometers of arterial road in East Java North Corridor is selected as case study and 2012 to 2014 crash data is analyzed. The Zero-Inflated Negative Binomial Model is preferred to develop crash prediction model with significant variables. This study has several findings. First, the number of median opening per unit length and disturbance level to pedestrian and road reserve area are the features that having positiverelationships with total accident count. Meanwhile, the ROW disturbance, conformance of intersection and of road marking also show significant value but negative relationship with total accident count. Second, significant variables for each type of crash may have different sign. For example, in right angle crash, median width has positive relation with the number of accident, while in run off and rear end crash, median width compliance is shown to have negative relation. Keywords: highway standard, accident prediction, arterial highway  Abstrak Kepatuhan terhadap standar merupakan doktrin utama dalam desain jalan, tapi hubungannya dengan jumlah kecelakaan belum banyak diteliti. Salah satu program utama dalam keselamatan jalan di Indonesia adalah pengujian laik fungsi jalan, yang dinilai dari pemenuhan jalan terhadap kiriteria dan spesifikasi desain nasional. Sejalan dengan perbaikan sistem pendataan kecelakaan di jalan di Indonesia saat ini, penelitian ini dilakukan untuk mengembangkan model untuk memprediksi jumlah kecelakaan per jenis kecelakaan dan mengidentifikasi fitur jalan yang signifikan berdasarkan pemenuhan terhadap standar nasional. Sekitar 272.200 kilometer jalan arteri di Koridor Utara Jawa Timur dipilih sebagai studi kasus dan data kecelakaan tahun 2012-2014 dianalisis. Model Binomial Negatif Zero-Inflated dipilih untuk mengembangkan model prediksi kecelakaan dengan variabel-variabel yang signifikan. Penelitian ini menghasilkan beberapa temuan. Pertama, jumlah bukaan median per satuan panjang dan tingkat gangguan untuk pejalan kaki dan ruang milik jalan merupakan fitur yang memiliki hubungan positif dengan jumlah total kecelakaan. Sementara itu, gangguan pada ruang milik jalan ROW, kesesuaian persimpangan dan marka jalan juga signifikan namun mempunyai hubungan negatif dengan jumlah total kecelakaan. Kedua, variabel yang signifikan untuk setiap jenis kecelakaan mungkin memiliki tanda yang berbeda. Misalnya, pada kecelakaan dari samping (tegak lurus), lebar median memiliki hubungan positif dengan jumlah kecelakaan, sementara kecelakaan di bagian jalan yang  lurus, pemenuhan lebar median memiliki hubungan negatif. Kata-kata kunci: standar jalan, prediksi kecelakaan, jalan arteri